Introducing an enhanced friction model for developing inertia welding simulation: A computational solid mechanics approach - Meyghani, B. (Materials and Energy Research Center, 2021)
Numerical simulation of inertia welding attracts enormous research interest during the past decades. Extremely large plastic deformation and complicated frictional behavior make this simulation challenging. In this paper, Norton friction model is modified to be employed in a computational solid mechanics model of inertia welding. A continuous remeshing technique is used to avoid the mesh distortion problem. The results show that after 1.5 (s) the temperature reaches the maximum value of 1200 â. After that, a decreasing pattern is found for the welding temperature. Moreover, the maximum deformation of 6 mm is obtained. The stress increased to the maximum values of 975 MPa. Consequently, successful prediction of the temperature distribution, thermal history, equivalent plastic deformation, axial shortening and stress distribution is made. The comparisons between the results of this study and the literature showed that implementing the proposed methodology leads to achieving high accuracy results. Â© 2021, Materials and Energy Research Center. All rights reserved.